An added sense the detection of nuclear radiation - U.S. Atomic Energy Commission. Research Laboratory (Livermore, Ca. : U.S. Atomic Energy Commission, Research Laboratory)
Presents significant concepts associated with detector technology and shows various research activities at the AEC's Lawrence Livermore Laboratory to demonstrate the wide use and application of nuclear detectors
Title from container
Keywords: Nuclear counters; Radiation -- Measurement